THE EFFECT OF WORK EXPERIENCE AND CHARACTERISTICS OF JOBS ON EMPLOYEE WORK ACHIEVEMENT IN SHIPPING COMPANY - Indah ayu Johanda Putri (Social Sciences and Education Research Review, 2020)
The commitment itself is shaped through individual characteristics and job characteristics. High commitment will improve employee work performance, thus individual characteristics and job characteristics should logically be related to work performance. This study aims to determine the effect of work experience and job characteristics on employee’s work performance in shipping companies. Methodology of this study is quantitative research and will be test the relationship between independent and dependent variables, with a sample of managers at shipping company located in Surabaya. Independent variable is work experiences and job characteristic, dependent variable is work performance. The data analysis technique used in this study is multiple linear regression analysis. Based on the result, it is obtained that the effect of work experience and job characteristic on employee’s work performance which has a significance value below 0.05 is a work experience variable. Thus, the work experience variable has an influence on work performance, while job characteristics do not have any influence on work performance. The result of this analysis indicated that work experience variable has an influence on work performance, while job characteristics did not have an influence on work performance. Based on the result, it can be concluded that Work experience has a positive effect on work performance, while Job characteristics do not affect work performance. However, work experience and job characteristics simultaneously influence work performance.